Plasmablast, Memory B Cell, CD4+ T Cell, and Circulating Follicular Helper T Cell Responses to a Non-Replicating Modified Vaccinia Ankara Vaccine - Evan J. Anderson; Lilin Lai; Jens Wrammert; Sarah Kabbani; Yongxian Xu; Lalita Priyamvada; Heather Hill; Johannes B. Goll; Travis L. Jensen; Carol Kao; Inci Yildirim; Nadine Rouphael; et al. (Vaccines, 2020)
Background: Vaccinia is known to induce antibody and cellular responses. Plasmablast, circulating follicular helper T (cTFH) cells, cytokine-expressing CD4 T cells, and memory B cells were compared between subcutaneous (SC) and needle-free jet injection (JI) recipients of non-replicating modified vaccinia Ankara (MVA) vaccine. Methods: Vaccinia-naïve adults received MVA SC or by JI on Days 1 and 29. Vaccinia-specific antibodies were quantified by plaque reduction neutralization test (PRNT) and enzyme-linked immunosorbent assay. Plasmablast, cTFH, and cytokine-expressing CD4 T cells were assessed on Days 1, 8, 15, 29, 36, 43 (cTFH and CD4+ only) and 57. Memory B cells were measured on Days 1 and 57. Results: Of the 36 enrolled subjects, only 22 received both vaccinations and had evaluable specimens after the second vaccine. Plasmablasts peaked one week after each vaccine. Day 15 plasmablasts correlated with peak PRNT titers. cTFH peaked on Days 8 and 36 and correlated with Day 36 plasmablasts. CD4+ peaked at Day 29 and one-third produced ≥2 cytokines. Day 57 memory B cells ranged from 0.1% to 0.17% of IgG-secreting B cells. Conclusions: This study provides insights into the cellular responses to non-replicating MVA, currently used as a vector for a variety of novel vaccines.